Odpowiedź :
{x+y=-4
{2x-3y=2
x=-4-y
2(-4-y)-3y=2
x=-4-y
-8-2y-3y=2
x=-4-y
-5y=10|/-5
x=-4-y
y=-2
x=-4+2
y=-2
x=-2
y=-2
{2x-3y=2
x=-4-y
2(-4-y)-3y=2
x=-4-y
-8-2y-3y=2
x=-4-y
-5y=10|/-5
x=-4-y
y=-2
x=-4+2
y=-2
x=-2
y=-2
x+y=-4 | *(-2)
2x-3y=2
-2x - 2y = 8
2x - 3y = 2
+---------------
-5y = 10
y = -2
x - 2 = -4
x = -2
y = -2
2x-3y=2
-2x - 2y = 8
2x - 3y = 2
+---------------
-5y = 10
y = -2
x - 2 = -4
x = -2
y = -2
x=-4-y
2x-3y=2
x= -4-y
2*(-4-y) - 3y=2
x=-4-y
-8 - 2y-3y=2
x= -4-y
- 5y=10
x=-4-y
y=-2
x=-4--2
y=-2
x=-2
y=-2
2x-3y=2
x= -4-y
2*(-4-y) - 3y=2
x=-4-y
-8 - 2y-3y=2
x= -4-y
- 5y=10
x=-4-y
y=-2
x=-4--2
y=-2
x=-2
y=-2